2017
DOI: 10.1155/2017/9343896
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Esophageal Adenocarcinoma with Urinary Bladder Metastasis

Abstract: Metastatic esophageal adenocarcinoma to the urinary bladder is extremely rare. We describe a previously healthy 49-year-old female with recent diagnosis of adenocarcinoma of the gastroesophageal junction with metastatic disease to the liver. Biopsy was positive for human epidermal growth factor receptor 2 (HER2) by Fluorescence In Situ Hybridization (FISH). She received six cycles of Cisplatin, 5-Fluorouracil, and Herceptin and subsequently developed symptomatic anemia and hematuria. Cystoscopy with retroflexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This was diagnosed as part of staging of the esophageal cancer and was treated with palliative radiotherapy. Katz et al [8] in 2017 reported a patient with esophageal cancer and staging scan showed metastatic liver lesions with retroperitoneal adenopathy. She completed chemotherapy, but developed anaemia with hematuria and was subsequently found to have metastatic esophageal cancer to the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…This was diagnosed as part of staging of the esophageal cancer and was treated with palliative radiotherapy. Katz et al [8] in 2017 reported a patient with esophageal cancer and staging scan showed metastatic liver lesions with retroperitoneal adenopathy. She completed chemotherapy, but developed anaemia with hematuria and was subsequently found to have metastatic esophageal cancer to the bladder.…”
Section: Discussionmentioning
confidence: 99%